The Impact of Keji Fuli on Adolescent Self-Expression in Contemporary China - Ruiming Zhao (Art and Society, 2025)
This paper examines the influence of Keji Fuli, a Confucian principle emphasizing self-restraint and adherence to social propriety, on adolescent self-expression in contemporary China. Despite modernization and digital transformation, Confucian ideals continue to shape youth identity, social interactions, and cultural expectations. Through family expectations, education, peer influences, and digital platforms, adolescent self-expression remains highly curated, balancing individuality with social conformity. While social media offers new opportunities, it also reinforces traditional values through self-censorship, indirect communication, and state regulation. Rather than rejecting Keji Fuli, many youth reinterpret it, blending tradition with modern identity in ways that reflect both constraint and innovation.